(untitled) (Bangladesh Journal of Zoology, 2018)
A field experiment was carried out in Gazipur, Bangladesh to find out the abundance and behavior of native insect pollinators and their impact on the yield and seed quality of mustard (Brassica juncea L.). Total 8 species of insects under 8 different families in 3 orders were found as pollinator and their abundance ranged from 0.5 to 6.6/30 sweeps. The pollinator insects revealed statistically higher abundance compared to pest, predator and other category. The pollinators were most abundant at 11.0 hrs of the day and differed in their landing duration on flower. Ant and cabbage butterfly stayed statistically similar and longer time (24.1 and 23.5 sec., respectively). The highest yield (994.3 kg/ha) was obtained from insect managed pollination treatment followed by open (759.7 kg/ha) and enclosed condition (272.3 kg/ha). Insect pollination revealed higher percentage of germination, t100-seed weight, per cent oil and protein content but the results did not differ statistically. Bangladesh J. Zool. 46(2): 117-123, 2018